Influence Of Labour-related Factors On Construction Labour Productivity In The South-south Geo-political Zone Of Nigeria - Odesola, Isaac Abiodun; Idoro, Godwin Iroroakpo (Penerbit Universiti Sains Malaysia, 2014)
Construction labour productivity has continued to be investigated because of its importance in national economies. This study assesses and compares the relative effects of labour-related factors on construction labour productivity across the six geographical states that comprise the south-south zone of Nigeria from the perspectives of building craftsmen and project supervisors/engineers. A field survey involving a stratified random sample of 1,138 building craftsmen and 561 project supervisors/engineers was conducted. Data were collected through structured questionnaires and analysed using mean item scores, KruskalWallis H-tests and Mann-Whitney U-tests. The results show that there is no significant influence of labour-related factors on construction labour productivity across geographical states, especially when they seem to be similar in terms of contiguity, linguistics, ethnicity, cultural practices, climate and socio-economic conditions. The two groups of respondents also agreed on the relative effects of labour-related factors on construction labour productivity. This study concludes that, when project locations are similar, labour management practices and productivities do not vary. 13 opportunities related to the management of labour for productivity improvement on building sites were emphasised. The study recommends that improved labour management practices are a potent productivity improvement strategy that will enhance construction labour productivity